REFLEKSI NILAI BUDAYA DALAM UNGKAPAN TRADISIONAL MASYARAKAT LUBUKLINGGAU SUMATERA SELATAN - Hasanadi Hasanadi (JURNAL PENELITIAN SEJARAH DAN BUDAYA, 2019)
This research investigates cultural values reflection existing within Lubuklinggau community in South Sumatera Province through several of traditional expressions. They are: 1) Expression of payu ponga nilek ngelup. Jengan melawan wang tue nilek meresak; (2) Expression of awak tue betunak dǝak hiyang melam kire nak ngelong; (3) Expression of lah ngidar lah baputar lom dǝpat jelan  hatuju; (4) Expression of makan ati nenggung sedingan rube abis resan urung; (5) Expression of lambat bekat gǝcang dǝpat. By using literary sociological approach and reinforced by hermeneutic analysis, it was concluded the five expressions reflect the cultural values of Lubuklinggau community, especially related to several life aspect, namely: (1) The need for a perennial commitment to be consistent and obedient to parents; (2) The importance of wife presence as a life partner and the significance of maintaining the integrity of family; (3) The need for knowledge in understanding the dynamics of dialogue that arises within community; (4) The need to compromise in maintaining friendship and healthy relationship amidst citizens; and (5) The importance of accurateness as well as swiftness in every field of engaged business.Keywords: cultural values reflections, traditional expressions, Lubuklinggau